Labor Markets in Low and Middle-Income Countries : Trends and Implications for Social Protection and Labor Policies - Cho, Yoonyoung; Margolis, David N.; Newhouse, David; Robalino, David A. (World Bank, Washington, DC, 2013)
This paper reviews labor market trends throughout the developing world, identifies issues and policy priorities across groups of countries, and derives implications for the World Bank's new social protection and labor strategy. Five key issues are identified: a high and growing share of the labor force that is self?employed or working in household enterprises, exposure to income shocks with limited access to risk management systems, low female participation rates, high youth unemployment rates, and the need to manage migration flows and remittances. The paper then details a three pronged agenda based on providing incentives and conditions for work, improving the efficiency of job creation, and managing risks / facilitating labor market transitions. This suggests that the Bank should emphasize self?employment and entrepreneurship promotion, provision of skills and development opportunities, and facilitation of labor market transitions into and between jobs, while protecting workers from shocks and paying particular attention to youth.